2019
DOI: 10.14366/usg.18062
|View full text |Cite
|
Sign up to set email alerts
|

Elastography of focal testicular lesions: current concepts and utility

Abstract: As a relatively new sonographic technique, tissue elastography has emerged as a qualitative and potentially quantitative adjunctive tool to provide additional information on tissue stiffness, aiming to further improve diagnostic confidence in discriminating benign from malignant focal testicular lesions. The purpose of this review is to provide an overview of the elastography techniques used to assess focal testicular lesions and their typical appearance on tissue elastography.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(49 citation statements)
references
References 32 publications
1
47
0
1
Order By: Relevance
“…The inclusion criteria of the study were as follows: (1) having been diagnosed with left-sided grade 1-3 varicocele on physical examination, (2) having Doppler and grayscale US findings that satisfied the criteria for varicocele, and (3) being between 18 and 50 years old. Patients with (1) chromosomal disorders, (2) a history of previous surgery, (3) present or previous malignancy, (4) bilateral or right-sided varicocele, (5) abnormal hormone levels, (6) chronic illness, (7) a history of radiation exposure, (8) hydrocele, (9) abnormal testicular parenchymal texture on US, and (10) teratozoospermia were excluded from the study. The healthy control group comprised randomly chosen patients who presented to our andrology clinic for infertility, but had normal testicular US, physical examinations, and laboratory results and were in couples that were ultimately diagnosed with female factor infertility.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The inclusion criteria of the study were as follows: (1) having been diagnosed with left-sided grade 1-3 varicocele on physical examination, (2) having Doppler and grayscale US findings that satisfied the criteria for varicocele, and (3) being between 18 and 50 years old. Patients with (1) chromosomal disorders, (2) a history of previous surgery, (3) present or previous malignancy, (4) bilateral or right-sided varicocele, (5) abnormal hormone levels, (6) chronic illness, (7) a history of radiation exposure, (8) hydrocele, (9) abnormal testicular parenchymal texture on US, and (10) teratozoospermia were excluded from the study. The healthy control group comprised randomly chosen patients who presented to our andrology clinic for infertility, but had normal testicular US, physical examinations, and laboratory results and were in couples that were ultimately diagnosed with female factor infertility.…”
Section: Methodsmentioning
confidence: 99%
“…SWE provides quantitative information regarding the stiffness of the relevant tissue by tracking shear waves passing through them [ 5 ]. The diagnostic value of elastography has been explored in undescended testes, testicular tumors, hydrocele, and testicular microlithiasis, with favorable results [ 5 - 8 ]. Several studies have investigated the role of SWE in assessing testicular parenchyma and the associations between SWE values and sperm parameters in the presence of varicocele.…”
Section: Introductionmentioning
confidence: 99%
“…Those lesions with VES > 3 may represent malignant lesions (sensitivity ~ 81.1-100%) with exceptions being testicular epidermoid and dermoid. 5,6 MRI can be used to differentiate benign and metastatic lesions with high accuracy. 4 EPR is regarded as an aggressive tumor with 26-71% of cases presenting with metastases to para-aortic and iliac nodes, hematogenous spread to lung, liver and bones.…”
Section: Discussionmentioning
confidence: 99%
“…Many investigators have reported the potential value of strain elastography as part of an mpUS assessment of focal testicular lesions and as a guide to malignancy; unfortunately, there is a lack of consistency between visual assessment scales, strain ratio values and differences between different US systems in these studies, making direct comparison problematic. One report revealed very high accuracy for strain elastography in identifying malignant lesions (Goddi et al 2012); however, the majority of studies report that it has a high sensitivity but low specificity for differentiation between benign and malignant lesions (Schr€ oder et al 2016;Fang et al 2019). It is also unclear whether visual assessment scores are more or less accurate than strain ratios in determining the likelihood of malignancy (Pozza et al 2016;Konstantatou et al 2019).…”
Section: Ultrasoundmentioning
confidence: 99%